Effects on oestrus duration of West African dwarf goats - Akusu, M.O.; Egbunike, G.N. (Elsevier, 1990)
Standing oestrus in west African dwarf goats averaged 31.1±1.7 h. Oestrus duration was not affected by time of day, although significantly more does (p